Computer Ethics and Professional Responsibility - Bynum, Terrell Ward; Rogerson, Simon (Blackwell Pub., 2004)
Keywords: Electronic data processing; Moral and ethical aspects; dept.phi; faculty_collection

The Blackwell Guide to American Philosophy - Marsoobian, Armen; Ryder, John (Blackwell Pub., 2004)
Keywords: Philosophy; American; dept.phi; faculty_collection

The Book of Love and Pain: Thinking at the Limit with Freud and Lacan - Nasio, Juan-David (State University of New York Press, 2004)
"In The Book of Love and Pain, Juan-David Nasio offers the first exclusive treatment of psychic pain in Freudian and Lacanian psychoanalytic literature. Using insights gained from more than three decades as a practicing psychoanalyst, Nasio addresses the limits faced by the analyst in attempting to think and treat pain psychoanalytically. He suggests that while pain is about separation and loss, psychic pain is intensified by paradoxical overinvestment in the lost loved one. Included are discussions of the pain of mourning, the pain of jouissance, unconscious pain, pain as an object of the drive, pain as a form of sexuality, pain and the scream, and the pain of silence. In offering a phenomenological description of psychic pain, The Book of Love and Pain fills a gaping void in psychoanalytic research and will play an important role in our understanding of the human psyche. Book jacket."–Jacket.
Keywords: Pain; Psychological aspects; Psychoanalysis; Stress; Psychological; dept.phi; faculty_collection; methods; psychology; Psychoanalytic Theory; Psychoanalytic Therapy; therapy; Bereavement; Pain

Probability and Tempered Modal Eliminativism - Shaffer, M.J. (History and Philosophy of Logic, 2004)
In this paper the strategy for the eliminative reduction of the alethic modalities suggested by John Venn is outlined and it is shown to anticipate certain related contemporary empiricistic and nominalistic projects. Venn attempted to reduce the alethic modalities to probabilities, and thus suggested a promising solution to the nagging issue of the inclusion of modal statements in empiricistic philosophical systems. However, despite the promise that this suggestion held for laying the ‘ghost of modality’ to rest, this general approach, tempered modal eliminativism, is shown to be inadequate for that task. © 2004 Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phi

Ethical challenges to citizens of ‘The automatic Age’: Norbert Wiener on the information society - Bynum, Terrell Ward (Journal of Information, Communication and Ethics in Society, 2004)
This article discusses the foresight of philosopher/mathematician Norbert Wiener who, in the 1940s, founded Information Ethics as a research discipline. Wiener envisioned the coming of an “automatic age” in which information technology would have profound social and ethical impacts upon the world. He predicted, for example, machines that will learn, reason and play games; “automatic factories” that will replace assembly-line workers and middle managers with computerized devices; workers who will perform their jobs over great distances with the aid of new communication technologies; and people who will gain remarkable powers by adding computerized “prostheses” to their bodies. To analyze the ethical implications of such developments, Wiener presented some principles of justice and employed a powerful practical method of ethical analysis. © 2004, Emerald Group Publishing Limited
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/069-878-157-439-708 tex.type: [object Object]
Keywords: Human purposes; Information ethics; Justice; dept.phi; peer-reviewed